The MedITNet assessment framework: development and validation of a framework for improving risk management of medical IT networks. Issue 9 (21st April 2016) - MacMahon, Silvana Togneri; McCaffery, Fergal; Keenan, Frank
Abstract: The use of networked medical devices can provide a number of benefits such as improved patient safety, a reduction in adverse events and reduced costs of care. Today, medical devices are increasingly designed for incorporation into a hospital's general IT network, which allows devices to exchange critical information. However, connecting devices in this way can introduce risks potentially negating the benefits to patients. While the IEC 80001‐1 standard has been developed to aid Healthcare Delivery Organisations (HDOs) in addressing these risks, HDOs often struggle to understand and implement the requirements. The MedITNet framework has been developed to allow HDOs to assess the capability of their risk management processes against the requirements of IEC 80001‐1. MedITNet provides a flexible assessment framework enabling HDOs to gain a greater understanding of the requirements of the standard and to improve risk management processes by determining their current state and highlighting areas for improvement. This paper examines the challenges faced by HDOs in the risk management of medical IT networks and briefly explains the components of the MedITNet framework and how the framework addresses these challenges. The use of Action Design Research (ADR) in the development and validation of MedITNet is also discussed focusing on a pilot implementation of the assessment method and expert review of the overall framework. The changes to the framework and its components as a result of the validation process are also discussed. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : This paper discusses how Action Design Research has been used in the development of the MedITNet Framework. MedITNet is a flexible assessment framework which can be used by Healthcare Delivery Organisations to assess the capability of their risk management processes related to medical IT networks. Improving risk management of medical IT networks ensures that the potential benefits of networked medical devices are realised and adverse events related to safety, effectiveness and security are avoided.